PENGARUH RELIABILITY,TANGIBILITY, ASSURANCE, EMPATHY, DAN RESPONSIVENESS TERHADAP CONSUMER SATISFACTION PADA JASA PERBANDARAAN SELAMA PANDEMI COVID-19 - Basmalasari, Rizky Mulia; Nugroho, Dian Ari (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2022)
This study aims to identify the effects of reliability, tangibility, assurance, empathy, and responsiveness on consumer satisfaction. The population of this research are all users of airport service provided by PT. Angkasa Pura II, from which 170 respondents were selected as the sample, to whom questionnaires were distributed online for data harvesting. This study is categorized as an explanatory research, which is generally used to explain the effects of reliability, tangibility, assurance, empathy, and responsiveness on consumer satisfaction during the Covid-19 pandemic. The data was analyzed using IBM SPSS (Statistical Package for the Social Sciences) version 25. The analysis includes instrument test (validity and reliability tests), classical assumption test (normality, multicollinearity, and heteroscedasticity tests), and hypothesis test (multiple linear regression, goodness-of-fit, coefficient of determination, and t tests). This study finds that tangibility, empathy, and responsiveness significantly influence consumer satisfaction and that assurance and empathy do not affect consumer satisfaction among customers of PT. Angkasa Pura II during the Covid-19 pandemic.